Management of Anxiety on Nurses in Facing Covid-19 at DKT Hospital Bandar Lampung - Endang Budiati; Yulistina Yulistina; Khaeriyah Khaeriyah; Dian Utama Pratiwi Putri (GLOBAL HEALTH SCIENCE GROUP, 2022)
Anxiety is an early symptom of psychological disorders and is still very possible to overcome, so it is necessary to study the condition of anxiety in health workers in various worlds during the Covid-19 pandemic to be opened and studied so as not to interfere or even turn off health services that affect the handling of the Covid-19 pandemic. The purpose of this study was to analyze the problems that exist in DKT TK IV Hospital 02.07.04 Bandar Lampung, especially the anxiety of nurses in dealing with Covid-19 and find alternative solutions to the problem. The method used in this study is an observational qualitative research aimed at examining the anxiety level of nurses who have not been educated and the level of anxiety of nurses who have been educated. Data were collected through in-depth interviews, observation and review of supporting documents. Data analysis used the concept of triangulation of sources, methods, and theories. There were 12 informants in this study, consisting of nurses in the isolation room at DKT Hospital in Bandar Lampung. Sampling with Random Sampling technique. Data collection tools used questionnaires and observation sheets, then the data analysis was univariate and bivariate using the chi square test. The author responded with the help of a questionnaire consisting of 14 questions in a questionnaire to 12 nurses who were nurses in the isolation room of the DKT Hospital in Bandar Lampung. Based on the questionnaire data distributed to 12 nurses in the isolation room, it was found that the anxiety level of nurses in the mild category was 1 person with a score of 19, and 11 others with moderate anxiety level with scores varying from 20-26. The causes of anxiety in nurses at DKT TK IV Hospital 02.07.04 Bandar Lampung are high workloads, use of PPE, lack of social and logistical support, and training support. After analyzing anxiety problems and their causes, alternative solutions are arranged to be implemented. The implemented solutions include the formation of battle buddies, training on coping strategies and social and logistical support. After taking steps to manage anxiety, the anxiety level of nurses in the isolation room who previously experienced moderate anxiety levels became mild and there was a decrease in anxiety scores by a percentage of 35.8%.